Diagnóstico de tuberculosis Desde Robert Koch hasta la actualidad - Díaz, Gustavo (Universidad Santiago de Cali, 2020)
Until the end of the 19th century, the diagnosis of tuberculosis (TB) rested solely on clinical approaches. Subsequently, Koch laid the foundations of the microbiological diagnosis of TB: microscopy and culture of Mycobacterium tuberculosis (Mtb). Today, these techniques remain as the basis for routine TB diagnosis in many countries. In fact, culturing Mtb is the gold standard for both diagnosis and TB treatment follow-up, either in solid (Lowenstein-Jensen, Ogawa, 7H11) or liquid culture systems (MGIT960, Proskauer-Beck, 7H9, among others). The advent of molecular methodologies led to the development of GeneXpert MTB/RIF (amplification of rpoB to identify Mtb and resistance to rifampicin, directly from sputum samples). Other molecular methods include LAMP-TB: isothermal amplification of IS6110 and gyrB, LPA: detection of resistance to first- and second-line drugs using DNA probes in nitrocellulose strips. The challenge imposed by the diagnosis of co-infected TB/HIV patients led to the development of LAM-TB. The latter method is based on the detection of Lipoarabinomannan in the urine of severely immunocompromised individuals with HIV-AIDS. Currently, the search for biomarkers in serum and urine represents a promising alternative. Metabolites, microRNAs and proteins derived from both Mtb and the human host have been also sought. In the last decades, the application of "omics" sciences has been decisive for the search of new TB biomarkers for diagnosis and prognosis.